The Use of Show and Tell Method to Teach English Speaking Skill - Sela, Sela; Rosnija, Eni; Wardah, Wardah (FKIP - Universitas Tanjungpura, 2025)
This study aims to determine the effectiveness of the shadow and tell method in teaching English-speaking skills to eighth-grade students. Using the Show and Tell method, students are given the opportunity to explain an item that is engaging in increasing their interest in practicing speaking in class. A pre-experimental research design was used with one group pre-test and post-test involving 30 students. The sample was chosen by applying cluster random sampling technique. The data of students